Book Review: Language Curriculum Design - Iswahyudi, Sabrina Retnasari (Har Press Indonesia, 2022)
This is a review of a book entitled Language Curriculum Design by I.S.P Nation & John Macalister. It provides analysis and criticism of the language curriculum design. The language curriculum design book describes the process of curriculum creation in detail and offers chances for practice and application. Since creating a curriculum or course is primarily a